Assessing the role of digital platforms in enhancing English proficiency among beginner-level Indonesian learners - Rusmiati Rusmiati; Delfia Herwanis; Rahmanita Zakaria; Hijjatul Qamariah (Universitas Muhammadiyah Malang, 2025)
This study explores the role of digital platforms in enhancing English proficiency among Indonesian learners. With the increasing demand for English language skills and the limitations of traditional classroom instruction, many learners have turned to online tools such as YouTube, Duolingo, and grammar websites to supplement their language learning. The study involved three female participants aged 18-24 from Indonesia, all of whom were beginner-level English learners. Data was collected through a questionnaire focusing on the participants’ use of online learning tools, the skills they prioritized, their satisfaction with the tools, and the challenges they encountered. The findings revealed that YouTube and Duolingo were the most popular tools, particularly for improving listening and speaking skills. The flexibility and accessibility of these platforms were highlighted as key advantages, although participants noted challenges such as a lack of real-time interaction with native speakers and difficulties maintaining motivation. Despite these challenges, the participants expressed general satisfaction with the tools and reported improvements in their English proficiency. This study concludes that while digital platforms are effective in developing receptive language skills, there is a need for improvements, particularly in fostering interaction with native speakers and addressing motivational barriers. The paper recommends incorporating real-time conversational features and more personalized content to further enhance the learning experience for Indonesian learners.